Review of Maternal Deaths in Lofa County, Liberia, 2015- 2017 - Tamba Saah Alpha; Darius Dolopei; Esther Argbah; Ngormbu Jusu Ballah; Lavala Bigboy Kortimai; Joseph Asamoah Frimgpong; Maame Amo-Addae; Peter Adewuyi; Olayinka Ilesanmi; Fulton Shannon; Himiede Wilson; Richard Kerkulah Vanyanteh Mulbah; et al. (Journal of Interventional Epidemiology and Public Health)
Introduction: Globally, 830 women die from pregnancy and childbirth daily. The maternal mortality ratio (MMR) in Liberia is 1072/100,000 live births. Maternal death is a priority event in Liberia, requiring immediate reporting. The causes and contributing factors of county-specific MMR are unknown. Therefore, data was analyzed to establish county MMR, and identify major causes and contributing factors of maternal death.